Atomic layer deposition technique refining oxygen vacancies in TiO2 passivation layer for photoelectrochemical ammonia synthesis. (January 2022) - Xu, Mengqiu; Xu, Fuchun; Zhu, Kaili; Xu, Xudong; Deng, Ping; Wu, Wenbo; Ye, Wei; Sun, Zhongti; Gao, Peng
Abstract: Photoelectrochemically (PEC) converting environmental pollutant nitrate back to valuable ammonia is a powerful complement to NH3 synthesis from Haber-Bosch process. Herein, atomic layer deposition (ALD) technique is employed to refine oxygen defect of TiO2 passivation layer on p-type silicon nanowire arrays to introduce active sites and improve the stability of silicon. Si@TiO2 -50-Vo nanowire arrays photocathode delivers a greatly enhanced NH3 yield rate of 1074 μgNH3 h −1 cm −2 and Faradaic efficiency (FE) of 94.3% at −0.6 V, as well as with excellent cycling stability. Theoretical calculations indicate that oxygen defect in passivation layer promotes the adsorption of nitrate and lowers the energy barrier of primary steps in NTRR. Graphical abstract: Oxygen defect in TiO2 passivation layer on p-type silicon nanowire arrays was refined by atomic layer deposition. TiO2 passivation layer with oxygen defect facilitates photo-generated electron/holes pairs separation, provides catalytic sites, as well as improves the cycling stability of Si photocathode. Si@TiO2 -Vo photocathode delivers a greatly enhanced PEC NTRR performance. Image 1 Highlights: Atomic layer deposition was used to refine oxygen vacancy in TiO2 . Oxygen vacancy in TiO2 passivation layer facilitates photo-generated electron/holes pairs separation. TiO2 passivation layer with oxygen defect on Si nanowire arrays boosted photoelectrochemical nitrate reduction to ammonia.